PKM Tiwir Farmer Group, Sumbersari Village to Increase Income by Cultivating Temulawak and White Turmeric and Their Processing Methods - Marwanti Mildaryani; Dwiyati Pujimulyani; Bayu Kanetro; Tri Indarto (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Most of the welfare of the people of Tiwir Hamlet, Sumbersari Sub-district is still below standard. Based on the survey results, the service team found that the Sumbersari Sub-district area, especially the Tiwir Hamlet, has many wild (not yet properly cultivated) plants growing rhizomes. Rhizome plants such as temulawak and temu mangga have not been optimally processed even though there are many vacant lands and small industries processing instant powder. This service aims to train and practice how to process temulawak and temu mangga into processed products as well as provide entrepreneurship and marketing training so that businesses can develop. This dedication partner is the Tiwir Farmers Group. Counseling and training activities were held on August 27 and September 3, 2022. The community became aware of the processing of instant powder of temulawak and temu mangga starting from cultivation, processing to marketing.